Areas of uncertainty in bridge management : framework for research - Onoufriou, Toula; Das, Parag C. (My University, 2000)
Bridge maintenance activities, from inspection and assessment to fund allocation and execution of the work, involve many uncertainties. If the predictably increasing future requirements for bridge maintenance are to be met in a cost-effective manner, these uncertainties must be identified and reduced as much as possible. Past research in bridge engineering has mostly concentrated on the engineering aspects of the activities. Many countries are now conducting considerable research and development efforts to produce better materials, innovative forms of construction, improved inspection and monitoring techniques, and better evaluation procedures and criteria. Now is the time to examine the uncertainties found in bridge management. To address these deficiencies, it is necessary to determine the focus of future research. Clearly, the level of resources that is used in different areas of research should reflect the accuracy that is warranted by the end use. On the basis of experiences gained from bridge management as well as from similar activities in the field of offshore structures, the areas of uncertainty, such as method sophistication, operator expertise, and human and sampling errors, are identified. In addition, a possible methodology is outlined that could provide bridge authorities, researchers, and industry with an overview of the currently perceived problems and their relative importance so that resources could be used in a cost-effective manner. The process of breaking down management into component activities by the use of flow diagrams and the representation of individual uncertainties through probabilistic distribution are also presented.
Keywords: Bridge